2016
DOI: 10.1111/scd.12197
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for treating patients with end‐stage renal disease: a survey of undergraduate dental programs

Abstract: There is a lack of consistent, established protocols among undergraduate dental programs. It is suggested that evidence-based guidelines for the safe treatment of patients be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
0
10
0
7
Order By: Relevance
“…To conclude, it needs emphasizing that the introducing schemes of prevention and treatment of dental ailments for patients with end-stage renal diseases to the curricula of medical studies is a topic currently under discussion [19].…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, it needs emphasizing that the introducing schemes of prevention and treatment of dental ailments for patients with end-stage renal diseases to the curricula of medical studies is a topic currently under discussion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus this study was developed to be conducted in three parts to collect data on the current antibiotic prophylactic protocols being utilized in patients with end‐stage renal disease in three different educational settings. The first part focused on dental schools and found that there was no consistent protocol for treating patients with ESRD . The second part focused on general practice residencies and advanced education in general dentistry residencies.…”
Section: Rationale/backgroundmentioning
confidence: 99%
“…The first and second parts surveyed dental schools and general dentistry residencies (advanced education and general practice) respectively. Both of those studies found that there were no consistent protocols for treating patients with ESRD . Over 50% of dental schools reported having no established renal patient treatment protocol.…”
Section: Rationale/backgroundmentioning
confidence: 99%